The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.06.02.543298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Phenotyping of the Lipidomic Response in COVID and non-COVID Sepsis

Hu Meng,
Arjun Sengupta,
Emanuela Ricciotti
et al.

Abstract: Lipids may influence cellular penetrance by pathogens and the immune response that they evoke. Here we find broad based lipidomic storm driven predominantly by secretory (s) phospholipase A2 (sPLA2) dependent eicosanoid production occurs in patients with sepsis of viral and bacterial origin and relates to disease severity in COVID-19. Elevations in the cyclooxygenase (COX) products of arachidonic acid (AA), PGD2 and PGI2, and the AA lipoxygenase (LOX) product, 12-HETE, and a reduction in the high abundance lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Analysis of patients with sepsis revealed that although PGD 2 is elevated in patients with sepsis of bacterial or viral origin, it has a relative selectivity for sepsis induced by SARS-CoV-2. 226 Indeed, genetic deletion or pharmacological inhibition of DPr1 protects aged mice from lethal SARS-CoV-2 infection. 227…”
Section: Pgf 2α In Vascular Remodelingmentioning
confidence: 99%
“…Analysis of patients with sepsis revealed that although PGD 2 is elevated in patients with sepsis of bacterial or viral origin, it has a relative selectivity for sepsis induced by SARS-CoV-2. 226 Indeed, genetic deletion or pharmacological inhibition of DPr1 protects aged mice from lethal SARS-CoV-2 infection. 227…”
Section: Pgf 2α In Vascular Remodelingmentioning
confidence: 99%